(untitled) (Swiss Medical Weekly, 2012)
Osteoporosis is characterised by a progressive loss of bone mass and microarchitecture which leads to increased fracture risk. Some of the drugs available to date have shown reductions in vertebral and non-vertebral fracture risk. However, in the ageing population of industrialised countries, still more fractures happen today than are avoided, which highlights the large medical need for new treatment options, models, and strategies. Recent insights into bone biology, have led to a better understanding of bone cell functions and crosstalk between osteoblasts, osteoclasts, and osteocytes at the molecular level. In the future, the armamentarium against osteoporotic fractures will likely be enriched by (1.) new bone anabolic substances such as antibodies directed against the endogenous inhibitors of bone formation sclerostin and dickkopf-1, PTH and PTHrp analogues, and possibly calcilytics; (2.) new inhibitors of bone resorption such as cathepsin K inhibitors which may suppress osteoclast function without impairing osteoclast viability and thus maintain bone formation by preserving the osteoclast-osteoblast crosstalk, and denosumab, an already widely available antibody against RANKL which inhibits osteoclast formation, function, and survival; and (3.) new therapeutic strategies based on an extended understanding of the pathophysiology of osteoporosis which may include sequential therapies with two or more bone active substances aimed at optimising the management of bone capital acquired during adolescence and maintained during adulthood in terms of both quantity and quality. Finally, one of the future challenges will be to identify those patients and patient populations expected to benefit the most from a given drug therapy or regimen. The WHO fracture risk assessment tool FRAX® and improved access to bone mineral density measurements by DXA will play a key role in this regard.